Bacteriophages Contribute to Shaping Clostridioides (Clostridium) difficile Species - Fortier, Louis-Charles (Frontiers in Microbiology, 2018)
Bacteriophages (phages) are bacterial viruses that parasitize bacteria. They are highly prevalent in nature, with an estimated 1031 viral particles in the whole biosphere, and they outnumber bacteria by at least 10-fold. Hence, phages represent important drivers of bacterial evolution, although our knowledge of the role played by phages in the mammalian gut is still embryonic. Several pathogens owe their virulence to the integrated phages (prophages) they harbor, which encode diverse virulence factors such as toxins. Clostridioides (Clostridium) difficile is an important opportunistic pathogen and several phages infecting this species have been described over the last decade. However, their exact contribution to the biology and virulence of this pathogen remains elusive. Current data have shown that C. difficile phages can alter virulence-associated phenotypes, in particular toxin production, by interfering with bacterial regulatory circuits through crosstalk with phage proteins for example. One phage has also been found to encode a complete binary toxin locus. Multiple regulatory genes have also been identified in phage genomes, suggesting that their impact on the host can be complex and often subtle. In this minireview, the current state of knowledge, major findings, and pending questions regarding C. difficile phages will be presented. In addition, with the apparent role played by phages in the success of fecal microbiota transplantation and the perspective of phage therapy for treatment of recurrent C. difficile infection, it has become even more crucial to understand what C. difficile phages do in the gut, how they impact their host, and how they influence the epidemiology and evolution of this clinically important pathogen.